Childhood transgenderity under the perspective of elementary school teachers - Francisca Vilena da Silva; Renata Dantas Jales; Ivoneide Lucena Pereira; Luana Rodrigues de Almeida; Jordana de Almeida Nogueira; Sandra Aparecida de Almeida (Universidade de São Paulo, 2021)
Objective: to analyze teachers' conceptions about transgenderity in childhood and to identify the possibilities and limits of working with these children in the school context. Method: a qualitative research study, carried out with 23 teachers from two municipal elementary schools. Semi-structured interviews were used to produce empirical material. As an analytical resource, the content analysis technique, thematic modality, was used. Results: six thematic categories emerged in the set of empirical material: There is transgenderity in childhood; The construction of gender identity and roles in childhood; The experience of trans children in the school context; Trans children: How to deal with?; Discussing the differences in the classroom: Is this the way?; and Dilemmas of school and family interaction. It was found that the gender dichotomy is reinforced in the classroom, causing tensions and stereotyped divisions for male and female roles. Various forms of violence have been reproduced by classmates and teachers, who, due to lack of knowledge or to unpreparedness, reinforce concepts and attitudes that lead to the maintenance of exclusion. Conclusion: the schools find it difficult to promote the inclusion of trans children. It is necessary to create strategies aimed at raising awareness and training the professionals who make up the school environment, especially teachers in the initial grades.